NCOG-38. CLINICAL CHARACTERISTICS OF LOW GRADE GLIOMA PATIENTS WITH NON-CANONICAL IDH1 AND IDH2 MUTATIONS. (9th November 2020) - Peters, Katherine; Lipp, Eric; Broadwater, Gloria; Herndon, James; Johnson, Margaret; Randazzo, Dina; Desjardins, Annick; Friedman, Henry; Ashley, David; Affronti, Mary
Abstract: BACKGROUND: Low grade gliomas (LGGs) develop in young adults and represent 10-15% of all glial tumors. While LGG patients can have longer survival than higher grade tumors, progression, transformation, and ultimately mortality occurs. Mutations in Isocitrate dehydrogenase 1/2 (IDH1/IDH2) are prevalent in LGG and are responsible for gliomagenesis. The classic IDH1 mutation is located at 132 codon and represented as p.Arg132His, but there are non-canonical IDH1 and IDH2 mutations. We sought to compare clinical characteristics of LGG patients with classic IDH1 p.Arg132His mutation to LGG patients with non-canonical IDH1 and IDH2 mutations. METHODS: We queried an IRB-approved registry retrospectively from 12/2004- 9/2019. We included IDH1/IDH2 mutant LGG (WHO grade II) and known IDH1 and IDH2 targeted mutation analysis using standard PCR followed by DNA sequencing to detect point mutations in IDH1/IDH2 genes. We obtained available clinical and histopathological data. We estimated progression-free survival (PFS), time to transformation (TT), and overall survival (OS) using Kaplan-Meier methods. RESULTS: We identified 267 LGG patients with median follow-up of 9.1 yrs (95%CI 8.4-9.9 yrs). Classic IDH1 p.Arg132His mutation occurred in 223 (83.9%) patients. IDH2 mutations occurred in 14 (5.2%) patients. Non-canonical IDH1 mutations were in 30 (11.2%) patients and included the following mutations: p.Arg132Cys (13), p.Arg132Gly (10), p.Arg132Ser (4), p.Arg132Leu (1), p.Arg119Gln (1), and p.Arg172Met (1). Initial presentation, OS, and TT did not differ between IDH1/IDH2 groups. PFS differed significantly between groups with improved median PFS in IDH2 mutant LGG (5.4 yrs; 95%CI 3.5-25.2) versus classic IDH1 mutant LGG (4.1 yrs; 95%CI 3.7-4.9 yrs) and non-canonical IDH1 mutant LGG (2.6 yrs; 95%CI 2.1-4.8) (log-rank p=0.019). Notably, non-canonical mutations were more common in astrocytoma (22/30; 73.3%) than other LGG histologies (p=0.018). CONCLUSIONS: In this cohort, LGG patients with non-canonical mutations have a shorter time to progression than patients with classic p.Arg132His mutation and IDH2 mutations.